TECHNIQUE DESIGN OF SPORT FISHING IN WATERS OF TOBA LAKE - Dedy Leonardi Siregar; Syafuddin '; Ronald Mangasi Hutauruk (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
ABSTRACTThis research was conducted in Countryside of Haranggaol, District of Sondi Raya, Sub-Province of Simalungun, Province of North Sumatera. It was April 2013 until September 2013. The objective of the research is to obtain the prinipal dimension of the new sport fishing in territorial water of Toba Lake. The methods to obtain such principal dimention is comparison ship methods by finding it about 6% above and below measure of owner requitment. The numbet of the comparison ship is 11. After analyzing by technique analyzes, it’s results for optmize vessel as LPP 7,5 m; B 3 m; H 1,2 m; T 1 m and total passenger 6-10 teps of especial size measure of optimasi is length 7,5m, wide 3m, high 1,2m, loaded 1m and amount of passenger counted 6 people. Desain general arrangement is provided in this research.Keyword: Sport of Fishing, Territorial Water of Lake of Toba, general arrangement.